Analisis Nilai Gizi dan Mutu Mikrobiologis Formula Enteral Tinggi Protein (FTP30) Berbahan Dasar Tepung Putih Telur (TEMU ILMIAH NASIONAL PERSAGI, 2023)
The most requested enteral formula in RSUD Dr. Soetomo is high protein enteral. This hospital made formula has short shelf life. FTP30 with white egg powder based is an innovative hospital formula with high amount of protein, 30 percent from total energy. White egg powder is chosen because of its high albumin amount. FTP30 is cheaper than other commercia l product and also has long shelf life. The aim of this study is to know about nutritional value and microbiological quality of FTP30. The design of this study is true experimental research on 9 samples with the ratio of skim milk and egg white powder i.e. P1 (50%:50%), P2 (60%:40%), P3 (70%:30%). The nutritional value is analyzed using Proximate Test. The results with Oneway ANOVA and Post Hoc Tukey analysis shows, there is no significant differences on energy amount, while the amount of protein, fat, carbohydrates and albumin are significantly different with p